2010
DOI: 10.1007/s10152-010-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic disturbance and spatial heterogeneity of macrobenthic invertebrate assemblages in coastal lagoons: the study case of Pialassa Baiona (northern Adriatic Sea)

Abstract: The distribution patterns of macrobenthic invertebrate assemblages at different spatial scales and in relation to natural and anthropogenic disturbance gradients were investigated in the Pialassa Baiona, a eutrophic and polluted brackish coastal lagoon located along the Italian coast of the northern Adriatic Sea. This coastal lagoon shows a complex physiography with several shallow water ponds and channels separated by discontinuous artificial embankments. Environmental variables and macrobenthic invertebrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…and Gracilaria sp.) followed by dystrophic crises have been frequently observed during the summer, especially in the southern area (Ponti et al 2005). At present, the lagoon is exploited for recreational fishing, Manila clam (Ruditapes philippinarum) harvesting, regulated hunting, leisure and cultural activities such as canoeing, guided walking tours and bird watching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Gracilaria sp.) followed by dystrophic crises have been frequently observed during the summer, especially in the southern area (Ponti et al 2005). At present, the lagoon is exploited for recreational fishing, Manila clam (Ruditapes philippinarum) harvesting, regulated hunting, leisure and cultural activities such as canoeing, guided walking tours and bird watching.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of industrial facilities located in the vicinity of the lagoon include two thermoelectric power plants and various chemical plants, all located in the southern side of the lagoon. Nowadays, there is an increasing concern that the proximity of anthropogenic activities taking place near the lagoon could result in undue pressure on this coastal ecosystem (Donnini et al 2007;Ponti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to stimulating microbial metabolism, sediment oxygen demand and nutrient regeneration (Ferguson, Eyre, and Gay, 2003;Slomp et al, 1993), sedimentary organic matter is a major food source for benthic infauna (Cheng and Chang, 1999;Spilmont et al, 2009) despite its often refractory nature (Cheng, 1995). Variations in the delivery and bioavailability of organic matter and regenerated nutrients, therefore, might influence benthic infauna population dynamics (Cheng and Chang, 1999;Ponti, Casselli, and Abbiati, 2010;Sánchez-Moyano, García-Asencio, and García-Gómez, 2010). During this study, increases in the combined macroinfauna density were observed to significantly correlate (r ¼ 0.755, p¼ 0.001, n¼ 16) with increased sediment organic matter content (food supply) within the surface sediments of Coombabah Lake, indicating that sediment column organic matter content was a factor influencing the combined macrofauna population dynamics of Coombabah Lake on a relatively small spatial scale (e.g.,~500 m).…”
Section: Discussionmentioning
confidence: 99%
“…These ecosystems are very heterogeneous in physiography and hydrology (Ponti et al, 2011), due to the varying balance of water, salt, nutrients, particulate organic and inorganic matter (Orfanidis et al, 2008). They can receive freshwater from streams and brooks, runoff or groundwater, as well as seawater by the action of tides or waves.…”
Section: According To the Interpretation Manual Of European Union Habmentioning
confidence: 99%
“…Increasing of tourism pressure and the use of these ecosystems for different human activities such as aquaculture or fisheries has induced internal perturbations such as pollution or removal of indigenous species (Aliaume et al, 2007). In coastal lagoons, species distribution is affected by heterogeneity of the environmental variable, such as water depth, hydrodynamic conditions, sediment characteristics, as well as by sources of anthropogenic disturbance that could interact with natural heterogeneity affecting patterns of species distribution, species diversity and ecosystem functioning (Ponti et al, 2011). Sometimes it is difficult to distinguish between natural heterogeneity and human disturbance.…”
Section: Hazards and Conservation Managementmentioning
confidence: 99%